12/x^2+2x + 3/x^2+2x-2 = 1

0 голосов
52 просмотров

12/x^2+2x + 3/x^2+2x-2 = 1


Алгебра (50 баллов) | 52 просмотров
Дан 1 ответ
0 голосов

(12/(x^2+2x))-(3/(x^2+2x-2))=1 замена x^2+2x=t 12/t-3/(t-2)-1=0 приводим к общему знаменателю (12*(t-2)-3t-t*(t-2))/(t*(t-2))=0 (12t-24-3t-t^2+t)/(t*(t-2))=0 (12t-24-3t-t^2+2t)=0 (t*(t-2))<>0 -t^2+11t-24=0 t<>0 или t-2<>0 t^2-11t+24=0 t<>0 или t<>2 t1=3 ili t2=8 обратная замена 1)x^2+2x=3 x^2+2x-3=0 х1=-3 х2=1 1)x^2+2x=8 x^2+2x-8=0 х1=-4 х2=2 Ответ:-4,-3,1,2

(96 баллов)